Growth in Africa Under Peace and Market Reforms - Korbut, Olessia (IMF Working Papers; Working Paper, 2011)
Economic stagnation in Sub-Saharan Africa (SSA) has led several economists to question the region's ability to attain sustained economic growth, some of them arguing for the need to shift away from natural resource - based exports. Yet, we find that low growth has not been common to all SSA countries and that those that achieved political stability and significantly liberalized their economies experienced high growth in income per capita, as high as ASEAN-5 countries. This group of SSA countries attained high growth while maintaining their specialization in natural resource exports. Our analysis also rejects the hypothesis of reverse causality: that good growth performance allowed countries to attain political stability or liberalize their economies.